Pemanfaatan Limbah Minyak Jelantah dalam Pembuatan Sabun Padat: Program Pengabdian Masyarakat di Desa Kebanggan - Khoeriyyah, Fatimah Zahza; Muslihah, Niken istikhari; Lestari, Puji; Suyata, Suyata; Irmanto, Irmanto (Politeknik Negeri Jember, 2026)
Waste is unused material that comes from various human activities. One type of waste that is widely produced from household activities is used cooking oil. Used cooking oil is cooking oil that has been used repeatedly and has deteriorated, making it hazardous to health and the environmental ecosystem. Processing used cooking oil into solid soap is a simple, economical, and environmentally friendly innovation that can be applied on a household scale based on the principle of zero waste industry. This community service activity was carried out in collaboration with the Aisyiyah Branch in Kebanggan Village, Sumbang District, Banyumas, where most of the members are housewives. The main objective of the program was to raise environmental awareness while empowering partners through training in making solid soap from used cooking oil. The methods used included socialization on the dangers of used cooking oil waste, the practice of making solid soap using the cold process method, and the application of the soap produced for washing kitchen utensils. Evaluation was carried out through pre-tests and post-tests to assess the increase in community knowledge and skills. The results of the activity showed a significant increase in the participants' understanding and skills in processing used cooking oil into useful products with quality that meets the 2021 Indonesian National Standard (SNI).